Hubungan Pelatihan Keterampilan Dengan Pengetahuan Kader Tentang Peran Fungsi Sistem 5 Meja Di Posyandu Wilayah Kerja Puskesmas Jatinangor Kabupaten Sumedang - Fardila Elba; Risma Ristiani (stikes dharma husada bandung, 2019)
Integrated Service Posts or Posyandu are facilities that make it easier for people to get health services. In the implementation of posyandu which has an important role, one of them is a cadre. Cadres have a role and function in Posyandu activities, one of which is to implement a 5-table system in Posyandu, but in the 5-table system it has not run optimally, this can be done by several factors, one of which is knowledge. The purpose of this study is to study the relationship of training that discusses knowledge about roles and functions at the posyandu which is devoted to the 5 table system. This study is analytical using cross-sectional. The sample in this study was a cadre in the area of ​​Jatinangor Health Center. Sampling using the Proposiate Stratified random sampling technique with a sample of 83 respondents. Data analysis using Gamma test. The study showed a significant participation rate between training with knowledge level (p = 0,000). Participating in training that had been attended by cadres' knowledge about the role of the 5-table system in the work area of ​​the jatinangor health center in Sumedang district.